Brief Report: The Deletion of the Phosphatase Regulator NIPP1 Causes Progenitor Cell Expansion in the Adult Liver. (20th June 2016) - Boens, Shannah; Verbinnen, Iris; Verhulst, Stefaan; Szekér, Kathelijne; Ferreira, Monica; Gevaert, Thomas; Baes, Myriam; Roskams, Tania; van Grunsven, Leo A.; Van Eynde, Aleyde; Bollen, Mathieu
Abstract: The Ppp1r8 gene encodes NIPP1, a nuclear interactor of protein phosphatase PP1. The deletion of NIPP1 is embryonic lethal at the gastrulation stage, which has hampered its functional characterization in adult tissues. Here, we describe the effects of a conditional deletion of NIPP1 in mouse liver epithelial cells. Ppp1r8 −/− livers developed a ductular reaction, that is, bile-duct hyperplasia with associated fibrosis. The increased proliferation of biliary epithelial cells was at least partially due to an expansion of the progenitor cell compartment that was independent of liver injury. Gene-expression analysis confirmed an upregulation of progenitor cell markers in the liver knockout livers but showed no effect on the expression of liver-injury associated regulators of cholangiocyte differentiation markers. Consistent with an inhibitory effect of NIPP1 on progenitor cell proliferation, Ppp1r8 −/− livers displayed an increased sensitivity to diet-supplemented 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine, which also causes bile-duct hyperplasia through progenitor cell expansion. In contrast, the liver knockouts responded normally to injuries (partial hepatectomy, single CCl4 administration) that are restored through proliferation of differentiated parenchymal cells. Our data indicate that NIPP1 does not regulate the proliferation of hepatocytes but is a suppressor of biliary epithelial cell proliferation, including progenitor cells, in the adult liver. Abstract : NIPP1 controls the balance between liver epithelial cells.